Genetic homogeneity of in vitro raised plants of grapevine cv. crimson seedless revealed by ISSR and microsatellite markers - Nookaraju, A.; Agrawal, Dinesh C. (South African Journal of Botany, 2012)
The present study was conducted to test the clonal homogeneity of six month old tissue culture raised plants of grapevine cv. Crimson Seedless using Inter Simple Sequence Repeat (ISSR) and Simple Sequence Repeat (SSR) markers. Visible assessment of these in vitro raised plants maintained in polyhouse did not show any morphological differences among themselves. However, to test the genetic homogeneity of these plants, we screened 50 ISSR primers out of which, 22 primers produced scorable and repeatable bands. These 22 primers were used further for assessing genetic homogeneity of in vitro raised plants of Crimson Seedless. These 22 ISSR primers generated 134 distinct band classes with a total of 3216 scorable bands. All the primers showed uniform banding pattern for all the in vitro raised plants and the mother plant. In case of 5 SSR primers (VS I, VVMD5, VVS2, VMCNG4c8 and VVMD31) used, a total of 288 scorable bands were obtained. The allele sizes ranged from 98 to 254 bp. Allelic composition of 23 in vitro raised plants and the mother plant at 5 SSR loci did not show any polymorphism. The results of the two marker systems in the present study revealed the genetic uniformity among the in vitro raised plants demonstrating the reliability of in vitro propagation system used for the cultivar. (C) 2011 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Allele composition; Clonal fidelity; Inter Simple Sequence Repeats; Monomorphic bands; Tissue culture; Vitis vinifera L.